Prevention of Nausea and Vomiting in Cancer Patients - Aapro, Matti; Jordan, Karin; Feyer, Petra; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2013)
Treatment tolerance is a challenge for most cancer patients, and it is therefore essential that healthcare professionals (HCPs) are quick to recognize adverse events and implement management strategies to address them. Prevention of Nausea and Vomiting in Cancer Patients provides comprehensive guidance on managing nausea and vomiting, which are common and often severe adverse events experienced by patients receiving chemotherapy and radiotherapy. The book refers to the latest American Society of Clinical Oncology (ASCO), European Society of Medical Oncology (ESMO), and Multinational Association for Supportive Care in Cancer (MASCC) guidelines and will be a useful resource for oncologists, oncology fellows, general physicians, and other HCPs wishing to learn more about the effective management of chemotherapy-and radiotherapy-induced nausea and vomiting in cancer patients.
Introduction -- Pathophysiology and classification of chemotherapy-induced nausea and vomiting -- Risk factors associated with nausea and vomiting after chemotherapy -- Risk factors associated with nausea and vomiting after radiotherapy -- Antiemetic drugs -- Antiemetic prophylaxis of chemotherapy-induced nausea and vomiting -- Antiemetic prophylaxis of radiotherapy-induced nausea and vomiting -- Summary of the approach to treatment of chemotherapy-induced nausea and vomiting -- Conclusions and future directions.
Keywords: Medicine; Radiotherapy; Oncology; Medicine & Public Health; Oncology; Radiotherapy; Pharmacotherapy